EMOTION REGULATION IN MOTHERS AND YOUNG CHILDREN FACED WITH TRAUMA. Issue 3 (30th April 2015) - Pat‐Horenczyk, Ruth; Cohen, S.; Ziv, Y.; Achituv, M.; Asulin‐Peretz, L.; Blanchard, T.R.; Schiff, M.; Brom, D.
ABSTRACT The present study investigated maternal emotion regulation as mediating the association between maternal posttraumatic stress symptoms and children's emotional dysregulation in a community sample of 431 Israeli mothers and children exposed to trauma. Little is known about the specific pathways through which maternal posttraumatic symptoms and deficits in emotion regulation contribute to emotional dysregulation. Inspired by the intergenerational process of relational posttraumatic stress disorder (PTSD), in which posttraumatic distress is transmitted from mothers to children, we suggest an analogous concept of relational emotion regulation, by which maternal emotion regulation problems may contribute to child emotion regulation deficits. Child emotion regulation problems were measured using the Child Behavior Checklist‐Dysregulation Profile (CBCL‐DP; T.M. Achenbach & I. Rescorla, 2000), which is comprised of three subscales of the CBCL: Attention, Aggression, and Anxiety/Depression. Maternal PTSD symptoms were assessed by the Posttraumatic Diagnostic Scale (E.B. Foa, L. Cashman, L. Jaycox, & K. Perry, 1997) and maternal emotion regulation by the Difficulties in Emotion Regulation Scale (K.L. Gratz & L. Roemer, 2004). Results showed that the child's emotion regulation problems were associated with both maternal posttraumatic symptoms and maternal emotion dysregulation. Further, maternal emotion regulation mediated the association between maternal posttraumatic symptoms and the child's regulation deficits. These findings highlight the central role of mothers' emotion regulation skills in the aftermath of trauma as it relates to children's emotion regulation skills. The degree of mothers' regulatory skills in the context of posttraumatic stress symptoms reflects a key process through which the intergenerational transmission of trauma may occur. Study results have critical implications for planning and developing clinical interventions geared toward the treatment of families in the aftermath of trauma and, in particular, the enhancement of mothers' emotion regulation skills after trauma.